Initiating a sustainable community-based agritourism model of herbal garden in a rural area of Indonesia: perspectives from community members - Aris Widayati; Aji Winanta; Hari Widada; Nur Hikmah Pratiwi (Cogent Social Sciences)
Facilities for introducing and increasing knowledge about herbal medicine must be initiated, especially those aimed at the younger generation and students. One way to provide these facilities is by initiating an herbal garden, which is used for educational tourism purposes. The problem is how to design an educational herbal garden model whose management is based on community empowerment and ensures its sustainability. Therefore, this study aims to explore the perceptions of local communities in order to initiate an herbal education garden based on sustainable community empowerment. The research location is Semoyo Village, Patuk District, Gunung Kidul Regency, Yogyakarta Province, Indonesia. The selection of this village as a study location was based on the results of a preliminary study, which showed that community members were initiating a tourist village, which was initially a homestead farm. The study used a qualitative approach with data collection techniques through interviews. Respondents were selected purposively among residents. Data were analyzed thematically. Thirty-five respondents were interviewed. The nine themes that emerged were positive attitudes, a spirit of cooperation, innovation, routine maintenance, involvement of the younger generation, training, initiating small enterprises, as well as planting herbal plants in every resident’s yard to help provide raw materials for production units. The perspective of the people in the village towards the idea of an educational herbal garden is still focused on improving the household income rather than the interest of educating the younger generation. This research raises a vital implication that establishing agritourism based on herbal education involves a tug-of-war between the hope of increasing local community income and the mandate of educating young people. Therefore, more in-depth studies are needed to develop innovations so that the expectancies of residents can be realized and sustained. Furthermore, the results of this study can be a unique inspiration for other regions with similar contexts and goals.